2020
DOI: 10.2807/1560-7917.es.2020.25.42.2001624
|View full text |Cite
|
Sign up to set email alerts
|

A large national outbreak of COVID-19 linked to air travel, Ireland, summer 2020

Abstract: An outbreak of 59 cases of coronavirus disease (COVID-19) originated with 13 cases linked by a 7 h, 17% occupancy flight into Ireland, summer 2020. The flight-associated attack rate was 9.8-17.8%. Spread to 46 non-flight cases occurred country-wide. Asymptomatic/pre-symptomatic transmission in-flight from a point source is implicated by 99% homology across the virus genome in five cases travelling from three different continents. Restriction of movement on arrival and robust contact tracing can limit propagati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
1
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 21 publications
2
53
1
1
Order By: Relevance
“…Similar reports of SARS-CoV-2 being transmitted during flight have recently been published ( 3 , 4 , 16 , 17 ). Those reports, along with the findings we report, demonstrate the potential for SARS-CoV-2 to spread on long-haul flights.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Similar reports of SARS-CoV-2 being transmitted during flight have recently been published ( 3 , 4 , 16 , 17 ). Those reports, along with the findings we report, demonstrate the potential for SARS-CoV-2 to spread on long-haul flights.…”
Section: Discussionsupporting
confidence: 84%
“…These 7 passengers had been seated within 4 rows of each other during the ≈18-hour flight from Dubai to Auckland. Because recent studies have reported conflicting findings of the risks associated with in-flight transmission ( 2 – 4 ), we undertook a comprehensive investigation to determine the potential source of infection of these travelers.…”
mentioning
confidence: 99%
“…For instance, Lau et al (2020) showed that there was an association between international and domestic air traffic and the COVID-19 outbreak, especially the total number of flights from Hubei, China. Murphy et al (2020) revealed the link between national outbreak of COVID-19 and air travel in Ireland. Therefore, we also selected the total number of flights departing from and stopping over in all of the cities in Hubei Province (“number of flights” for short).…”
Section: Specification Of the Be Attributesmentioning
confidence: 99%
“…In addition to the potential transmission risk between passengers onboard planes, 8 travel of infected patients between countries is seen as an important vector of transmission before large-scale interventions were introduced. 10 Air travel is also a likely proxy of more general traffic between nations. The possible impact of those interventions, as well as testing for similarities in space and time between countries with different political, social and economic standing, is therefore of great interest.…”
Section: Introductionmentioning
confidence: 99%